Structural Modeling and Analysis of Pregnancy-Associated Glycoprotein-1 of Buffalo (Bubalus bubalis). (12th March 2012) - Andonissamy, Jerome; Singh, S. K.; Agarwal, S. K.
Abstract : The present study was conducted to design and analyze the structural model of buffalo pregnancy-associated glycoprotein-1 (PAG-1) using bioinformatics. Structural modeling of the deduced buffalo PAG-1 protein was done using PHYRE, CONSURF servers and its structure was subsequently constructed using MODELLER 9.9 and PyMOL softwares Buffalo PAG-1 structural conformity was analyzed using PROSA, WHATIF, and 3D-PSSM servers. Designed buffalo PAG-1 protein structure on BLAST analysis retrieved protein structures belonging to aspartic proteinase family. Moreover in silico analysis revealed buffalo PAG-1 protein retained bilobed structure with pepstatin-binding clefts near the active sites by docking studies with pepstatin A using PatchDock server. Structural studies revealed that the amino and carboxy terminal containing aspartic residues are highly conserved and buried within the protein structure. Structural conformity studies showed that more than 90% of the residues lie inside favored and allowed regions. It was also deduced that buffalo PAG-1 possesses low and high energy zones with a very low threshold for proteolysis ascertaining the stableness of the buffalo PAG-1 protein structure. This study depicts the structural conformity and stability of buffalo PAG-1 protein.